Optimization of Stock Investment Strategy with The Fibonacci Retracement Method to Determine Take Profit and Stop Loss - Ananda Saputri; Ifayani Haanurat; Asri Jaya (Green Publisher Indonesia, 2025)
This research aims to assess the effectiveness of Fibonacci retracement in establishing take profit and stop loss levels for stocks within the LQ45 Index. The study utilizes a quantitative approach with a descriptive method, analyzing daily stock price data from January 2021 to December 30, 2021, through the Fibonacci retracement indicator. The research sample comprises 10 companies listed in the LQ45 Index, selected based on specific criteria. The results demonstrate that Fibonacci retracement is effective in pinpointing significant levels for determining take profit and stop loss, achieving an effectiveness rate of 74%. Fibonacci levels such as 38.2% and 61.8% have proven to be crucial references in establishing take profit and stop loss positions. These findings endorse the use of Fibonacci retracement as a technical analysis tool capable of maximizing profit potential while minimizing losses, particularly in markets experiencing an uptrend or downtrend.